Equilibrium and non-equilibrium controls on the abundances of clumped isotopologues of methane during thermogenic formation in laboratory experiments: Implications for the chemistry of pyrolysis and the origins of natural gases. (15th February 2018) - Shuai, Yanhua; Douglas, Peter M.J.; Zhang, Shuichang; Stolper, Daniel A.; Ellis, Geoffrey S.; Lawson, Michael; Lewan, Michael D.; Formolo, Michael; Mi, Jingkui; He, Kun; Hu, Guoyi; Eiler, John M.
Abstract: Multiply isotopically substituted molecules ('clumped' isotopologues) can be used as geothermometers because their proportions at isotopic equilibrium relative to a random distribution of isotopes amongst all isotopologues are functions of temperature. This has allowed measurements of clumped-isotope abundances to be used to constrain formation temperatures of several natural materials. However, kinetic processes during generation, modification, or transport of natural materials can also affect their clumped-isotope compositions. Herein, we show that methane generated experimentally by closed-system hydrous pyrolysis of shale or nonhydrous pyrolysis of coal yields clumped-isotope compositions consistent with an equilibrium distribution of isotopologues under some experimental conditions (temperature–time conditions corresponding to 'low, ' 'mature, ' and 'over-mature' stages of catagenesis), but can have non-equilibrium (i.e., kinetically controlled) distributions under other experimental conditions ('high' to 'over-mature' stages), particularly for pyrolysis of coal. Non-equilibrium compositions, when present, lead the measured proportions of clumped species to be lower than expected for equilibrium at the experimental temperature, and in some cases to be lower than a random distribution of isotopes (i.e., negative Δ18 values). We propose that the consistency with equilibrium for methane formed by relatively low temperature pyrolysis reflects local reversibility of isotope exchange reactions involving a reactant or transition state species during demethylation of one or more components of kerogen. Non-equilibrium clumped-isotope compositions occur under conditions where 'secondary' cracking of retained oil in shale or wet gas hydrocarbons (C2-5, especially ethane) in coal is prominent. We suggest these non-equilibrium isotopic compositions are the result of the expression of kinetic isotope effects during the irreversible generation of methane from an alkyl precursor. Other interpretations are also explored. These findings provide new insights into the chemistry of thermogenic methane generation, and may provide an explanation of the elevated apparent temperatures recorded by the methane clumped-isotope thermometer in some natural gases. However, it remains unknown if the laboratory experiments capture the processes that occur at the longer time and lower temperatures of natural gas formation.